2023
DOI: 10.1002/adfm.202214529
|View full text |Cite
|
Sign up to set email alerts
|

Yolk‐Shell Structured Zinc‐Cobalt‐Ruthenium Alloy Oxide Assembled with Ultra‐Small Nanoparticles: A Superior Cascade Catalyst toward Oxygen Evolution Reaction

Abstract: Structure engineering has proven to be an effective strategy for improving the catalytic performance and reducing the cost of ruthenium oxide‐based catalysts toward oxygen evolution reactions (OER). Herein, a polyhedron‐shaped yolk‐shell structure composed of zinc‐cobalt‐ruthenium ternary metal alloy oxide (ZnCo‐RuO2/C) is prepared, by taking advantage of the Kirkendall effect. The yolk‐shell frame and the ensembled metal oxide nanoparticles are 116.9 ± 25.9 nm and 3.1 ± 0.7 nm in diameter, respectively. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[29,30]. The Co 2p of Fe2CoSe4@NC (Figure 3b) exhibits peaks at 780.3 and 796.3 eV, which are attributed to the Co 2+ 2p3/2 and 2p1/2 orbitals, accompanied with two satellite peaks at 785.9 and 802.8 eV, respectively [31][32][33][34][35]. As depicted in Figure 3e, the high-resolution XPS spectrum of Ni 2+ 2p comprises a pair of spin-orbit doublets at 854.6 and 873.2 eV, as well as two satellite peaks [36,37].…”
Section: Figurementioning
confidence: 98%
“…[29,30]. The Co 2p of Fe2CoSe4@NC (Figure 3b) exhibits peaks at 780.3 and 796.3 eV, which are attributed to the Co 2+ 2p3/2 and 2p1/2 orbitals, accompanied with two satellite peaks at 785.9 and 802.8 eV, respectively [31][32][33][34][35]. As depicted in Figure 3e, the high-resolution XPS spectrum of Ni 2+ 2p comprises a pair of spin-orbit doublets at 854.6 and 873.2 eV, as well as two satellite peaks [36,37].…”
Section: Figurementioning
confidence: 98%
“…The utilization efficiency of the active site can be significantly increased by the large surface area of the carrier carrying the active site. In addition, the coupling of metal particles or atoms with the carrier can induce significant electron transfer, which affects the adsorption of oxygen intermediates and thereby significantly enhances the activity and stability [ 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ]. Although Ru-based oxide electrocatalysts exhibit high initial OER activity due to their kinetically favorable lattice oxygen oxidation mechanisms, the high-valence oxygen hole intermediate species are highly soluble, resulting in decreased catalytic activity and stability in acidic electrolytes.…”
Section: Activity and Stability Enhancement Strategiesmentioning
confidence: 99%
“…Wu et al 34 demonstrated that the HE rocksalt (MgFeCoNiZn)O presents greater OER performance compared with single rocksalt oxides, which is attributed to the synergy effects between various components and an increase in active sites. Compared to the increase of the intrinsic properties of a material with conventional doping, 35 the structural and property changes resulting from the HE strategy are more signicant. Due to the complexity of HE materials, at present, the potential effects of HE design methods, which induce electronic structures and microstructure characteristics that affect the performance for acid-water oxidation, are elusive and remain unclear.…”
Section: Introductionmentioning
confidence: 99%